1964
DOI: 10.1021/jo01032a535
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Diethyl Malonate with Styrene Oxide

Abstract: l,l,7,7,tetrasiloxane.-To a solution of 0.390 g. (1.33 mmole.) of the tetrol in 40 ml. of ether was added 4.0 ml. (31.6 mmoles.) of trimethylchlorosilane and 2.0 ml. of pyridine. Work-up as above yielded 0.422 g. (57%) of distillate which mostly solidified to a waxy solid. Vapor phase chromatography showed this to be about 95% pure; a specimen collected by v.p.c. melted at 85-90°and had an infrared spectrum identical with that of a sample prepared by Simmler's2 procedure. This spectrum (in CS2) showed a very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1966
1966
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…II 0-Phenyl-7-butyrolactone (Ila), mp 46-47°, was isolated from the reaction of styrene oxide with sodiomalonic ester, as described earlier. [1][2][3] Its pmr spectrum corresponded with that described by DePuy and coworkers,1 and we therefore agree1,2 that a attack by diethyl malonate anion on styrene oxide is of greater importance than ß attack. 7-Phenyl-7-butyrolactone (la), mp 37°, was prepared5 by catalytic reduction of /3-benzoylpropionic acid.…”
Section: Experimental Section4supporting
confidence: 85%
“…II 0-Phenyl-7-butyrolactone (Ila), mp 46-47°, was isolated from the reaction of styrene oxide with sodiomalonic ester, as described earlier. [1][2][3] Its pmr spectrum corresponded with that described by DePuy and coworkers,1 and we therefore agree1,2 that a attack by diethyl malonate anion on styrene oxide is of greater importance than ß attack. 7-Phenyl-7-butyrolactone (la), mp 37°, was prepared5 by catalytic reduction of /3-benzoylpropionic acid.…”
Section: Experimental Section4supporting
confidence: 85%
“…Investigations into the behavior of styrene oxide in the presence of nucleophiles indicated that a mixture of products may be expected due to the electronic contributions of the benzene ring. 11,12 Oligomerization of the epoxide at the chain end is also possible, as has been observed for ethylene oxide under certain conditions. [4][5][6] A variety of analytical tools were utilized to determine the functionality, regiochemistry, and degree of oligomerization, including 1 H and 13 C NMR spectroscopy and MALDI-TOF MS.…”
Section: Resultsmentioning
confidence: 64%
“…11,12 The reaction of styrene oxide with sodium diethyl malonate resulted in the formation of two lactones. 11 The major product (60%) resulted from nucleophilic attack at the more hindered carbon, while the minor product resulted from attack at the least hindered carbon. Subsequent work on the ring opening of para-substituted styrene oxides indicated that the substituent had a dramatic effect on the regiochemistry of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl 2indanylacetate (21) was prepared by hydrogenolysis and subsequent esterification of the tricyclic lactone 20 (ABC part of GR24), as depicted in Scheme IV. ß• and 7-phenyl-7-butyrolactone were obtained as a mixture from styrene oxide and diethyl malonate (De Puy et al, 1964) and subsequently separated by chromatography. (7-Phenyl-7-butyrolactone is also commercially available.)…”
Section: Resultsmentioning
confidence: 99%